Legal issues of inter-Korean economic cooperation under the armistice system - Lee, Eric Yong-Joong (Kluwer Law International, 2002)
This book reviews the current legal regime and the setting up of a positive legal framework for inter-Korean economic cooperation, beginning to be regulated by international law at the start of the 21st century.